The Evaluation of the Impact of Informal Entrepreneurship on Poverty Alleviation in Nigeria - Alabi, Williams Omodara Alabi; Agboola, Oluyemisi Omobola; Fasanmi, Olumuyiwa Oladapo; Moses, Sodeinde Gbemi; Ayodele, Folasade Olusola Ayodele (African Journal of Stability and Development (AJSD), 2025)
This study appraised the contribution of informal entrepreneurship to poverty alleviation in Nigeria. Primary data was collected through the use of the questionnaire. Data was analysed using Analysis of Variance (ANOVA). Findings show that: trade and commerce (F=14.65,) has a significant influence on poverty alleviation because Prob>F =.0050 is less than the 0.05 level of significance; manufacturing with F value = 24.92 significantly influences poverty alleviation because the Prob>F = 0.0000 is less than the 0.05 level of significance. Also, the technical work with F value of 16.59 has a significant influence on poverty alleviation since Prob>F = 0.0000 is less than the 0.05 level of significance. Transportation, with F value of 7.52 and Prob>F = 0.0000, which is lower than 0.05 level of significance, significantly influences poverty alleviation. Farming with 4.41 F value significantly influences poverty alleviation because the Prob>F = 0.0016 is less than 0.05 level of significance. Service business also shows significant influence on poverty alleviation with F value of 5.58 and Prob>F = 0.0009, which is less than 0.05 level of significance. However, the model has F value of 22.92 and Prob>F value of 0.000, which is less than 0.05 level of significance. It is concluded that the aggregate income generated from informal entrepreneurship leads to a reduction in poverty; thus, the informal entrepreneurs should look inwardly at things eroding their income to maximise profit from their operations.